2016
DOI: 10.1515/hukin-2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Specific Sling Exercises on the Functional Movement Screen Score in Adolescent Volleyball Players: A Preliminary Study

Abstract: The existing data indicate that the result of the Functional Movement Screen (FMS) test influences the likelihood of subsequent injury in professional athletes. Therefore, exercises increasing test scores of the FMS may be useful at various stages of sports activity. This study evaluated the effects of the NEURAC sling exercises method on the FMS test score in teenage volleyball players. The study was conducted on 15 volleyball players aged 14 years. The FMS test was performed three times interspersed with a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 7 publications
3
23
0
Order By: Relevance
“…12 Studies investigating the effectiveness of the FMS to monitor training intervention have been conducted. 35,[45][46][47] al. 46 performed the first controlled trail using FMS to assess movement competency in secondary school children.…”
Section: Modifiabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…12 Studies investigating the effectiveness of the FMS to monitor training intervention have been conducted. 35,[45][46][47] al. 46 performed the first controlled trail using FMS to assess movement competency in secondary school children.…”
Section: Modifiabilitymentioning
confidence: 99%
“…On the contrary, there are other studies that have shown FMS scores can be improved through training interventions. 35,45,47 Cowen et al 35 examined FMS scores in active firefighters before and after a six week yoga program and found significant improvement in overall FMS scores. In another study conducted by Goss et al 47 FMS scores in a group of special operation soldiers were found to also improve in total score by an average of 2.5 points following a six-…”
Section: Modifiabilitymentioning
confidence: 99%
“…The authors thought that the exercises of this group not only provide jumping readiness improvement, but also present scientifically substantiated means of traumas prevention. Polish scientists studied the methodologies of steadiness training for volleyball players [9]. Experimentally substantiated were the complexes of exercises with loops, which were fulfilled 2 times a week during 2 months, exercises with balancing platform and fitball use, which were fulfilled every day during 10 days and also compression trousers.…”
Section: Resultsmentioning
confidence: 99%
“…In order to help motivate subjects to achieve maximal muscle activity, verbal encouragement was used. e average EMG of the 3 replicates was used in the analysis after normalization to %MVIC [5][6][7]15], and mean power frequency (MPF) was also recorded. To minimize muscle fatigue, a 1-minute break was taken after each muscle.…”
Section: Emg Recording and Data Processingmentioning
confidence: 99%
“…In recent decades, sling exercise has been used as an efficient training program for patients with musculoskeletal disorders [5][6][7].…”
Section: Introductionmentioning
confidence: 99%